21st Century Skills-Based Learning at Nahdlatul Ulama Higher Education (Case Study of Islamic Education Program (PAI) at UNISNU Jepara) - Rahmi, Yulia Savika; Saefudin, Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
21st-century education demands a more innovative approach to prepare students for future challenges. This article explores the implementation of 21st-century skills-based learning in the Islamic Religious Education (PAI) Study Program at the Nahdlatul Ulama Islamic University (UNISNU) Jepara. This study uses qualitative methods to analyze how 21st-century skills are integrated into the PAI curriculum and their impact on student learning outcomes. Despite notable achievements in implementing 21st-century skills, the study findings identified significant weaknesses in critical thinking skills among female students at UNISNU Jepara. This study encourages educators to explore alternative methods to improve critical thinking skills, ensuring students can apply them efficiently in different academic contexts. In addition, students are expected to actively foster curiosity, collaborate with peers and lecturers, and improve literacy skills by exploring various sources of information. Collaborative efforts between educators and students are vital to creating an environment that supports the continuous improvement of critical thinking skills, reflecting a commitment to excellence in education and skills development. This article offers insights and recommendations for faith-based higher education institutions to integrate 21st-century skills effectively.